Моніторинг інформації щодо використання пробіотичних систем на основі lactobacillus acidophilus у складі харчових продуктів - Большакова, В. Л. (НТУ "ХПІ", 2015)
Проаналізовано існуючі технології харчових та фармацевтичних продуктів на основі ацидофільної палички. Особливу увагу приділено виду пробіотичних мікроорганізмів Lactobacillus acidophilus (LA 5) та продуктів на його основі. Обґрунтовано ідею щодо використання капсульованих форм ацидофільної палички, як засобу пролонгації терміну зберігання продуктів без втрати їх пробіотичних властивостей та технологічної безпеки. Наведено прогнозовані можливості розширення асортименту харчових продуктів з ацидофільною паличкою.

The article is devoted to a detailed analysis of existing technologies of food and pharmaceutical products based on Lactobacillus acidophilus. Particular attention is given to mean the probiotic microorganism Lactobacillus acidophilus (LA 5) and products based on it. In this article, the emphasis is put on the fact that Lactobacillus acidophilus is extensively metabolized in nearly all food environments, while products of metabolism inhibit prolonged preservation of high consumer properties of goods. According to the results of the monitoring of existing information, identified problems are little understood and requires further research. The article explains the idea of using encapsulated Lactobacillus acidophilus forms as a means of prolonging the shelf life of products without losing their probiotic properties and process safety. Monitoring results can be the basis for technology products containing Lactobacillus acidophilus capsule forms that will greatly expand the range of goods with probiotic properties of this type of microorganisms. The article summarizes the new material on the subject in question, introduced into scientific use the term "encapsulated form of Lactobacillus acidophilus", "encapsulation of Lactobacillus acidophilus». The article analyzes the market of food and pharmaceutical products based acidophilic bacillus. Scientifically grounded new approach to increase the shelf life of such products by means of inclusion of probiotic microorganisms in resistant to acidsmembranes based on sodium alginate. Also in the article presented the possibility of expanding the range of projected food with acidophilus bacillus.
Monitoring of probiotic systems using based on lactobacillus acidophilus in the food
Keywords: капсульовані пробіотичні мікроорганізми; ацидофільна паличка; функціональні продукти; альгінатні оболонки; encapsulated probiotic microorganisms; acidophilus bacillus; functional products; alginate shells